Messenteric bowel infarction: Definition. Ethiopathogenesis. Pathophysiology. Pathological anatomy; introduction Carlos Ormaechea - Silva, Celso (Cirugía del Uruguay, 1972)
The etiopathogenesis, pathophysiology and pathological anatomy of intestinal infarction are successively studied.